Novel strategies for fortifying vegetable matrices with iron and Lactobacillus casei simultaneously - Genevois, Carolina Elizabeth (2017)
The aim of the work was to study the effects of simultaneous fortification, iron and Lactobacillus casei (L. casei) on a vegetable matrix. Pumpkin tissue was used as vegetable matrix for iron fortification in a dry infusion process and an edible coating containing L. casei was applied. Three systems were assayed: A) pumpkin fortified with iron and probiotic, B) pumpkin fortified with iron, and C) pumpkin fortified with probiotic. The chroma and b* changes during storage followed a first-order kinetic model. The combined presence of iron and probiotic delayed the textural change. The final product presented 0.35 mg of iron/g, where 50–58% was bioaccessible after the “in vitro” digestion. The probiotic concentration remained >107 CFU g−1 for 14 days and the viability was affected by the mineral incorporation. The presence of L. casei tended to improve the iron bioaccessibility by reducing insoluble iron content in simulated lumen conditions. The untrained sensory panel did not perceive differences due to iron presence, and both formulations received punctuations above 5- using a 7-point hedonic scale for overall acceptability being rated as “like slightly”.